E-Government Asset Management Using the Extreme Programming - Taqwa Hariguna; Mirra Tsamara (International Journal of Informatics and Information Systems, 2019)
Village Asset Management is a village property derived from the original property of the village, purchased or acquired for the expense of the village's income and expenditure budget (APBDes) or other legitimate acquisition of rights. In this study is the management of the village assets Kebumen Baturraden subdistrict and The problems acquired are the recording of village assets and the realization of the budget of the village assets that are still written so it takes A long time, Therefore the purpose in This research is to help and facilitate management performance in village Asset listing. Methods of collecting data using observations, interviews and Library studies. System development method using the Extreme programming method consisting of four phases of system development, namely planning, design, coding and test. The result of this research is a Village Asset Management E-Government using the Extreme Programming method of the Kebumen Village case study. The conclusion of this research is that it can simplify the management and realization of village assets budget due to the two interconnected reporting are reports of budget realization and village Asset report.